Priority issues and approaches in assessing the effectiveness of student health - Naumenko, N. A.; Kutsekon, A. A.; Kindrat, E. A.; Sokolovskaya, I. A.; Науменко, Н. А.; Куцеконь, А. А.; Киндрат, Е. А.; Соколовская, И. А.; Соколовська, Ірина Анатоліївна (My University, 2021)
Health is an invaluable asset not only of the individual, but also of the people, the nation, the state. Of particular importance is the need to develop priorities and basic principles for the formation of methods of rehabilitation and disease prevention among young people in the context of the studied problem of modern society, which is experiencing a health crisis.Здоровье - бесценный капитал не только отдельного человека, но и народа, нации, государства. В контексте исследуемой проблемы современного общества, внутри которого манифестирует кризис здоровья, особое значение приобретает необходимость разработки приоритетных направлений и главных принципов в формировании подходов к оздоровлению и профилактике заболеваний у молодежи.
Приоритетные вопросы и подходы в оценке эффективности оздоровления студенчества
Keywords: health; wellness; students; prevention; здоровье; оздоровление; студенты; профилактика